An efficient perturbation method to predict the functionally key sites of glutamine binding protein. (April 2017) - Lv, Dashuai; Wang, Cunxin; Li, Chunhua; Tan, Jianjun; Zhang, Xiaoyi
Graphical abstract: Highlights: Use of a coarse-grained method to predict key residues in a protein. A thermodynamic cycle was applied to calculate the free energy changes. The residues with relatively large ΔΔ G values are considered to be key residues. Key residues in 19 clusters distributed in different regions were identified. Abstract: Glutamine-Binding Protein (GlnBP) of Escherichia coli, an important member of the periplasmic binding protein family, is responsible for the first step in the active transport of glutamine across the cytoplasmic membrane. In this work, the functionally key regulation sites of GlnBP were identified by utilizing a perturbation method proposed by our group, in which the residues whose perturbations markedly change the binding free energy between GlnBP and glutamine are considered to be functionally key residues. The results show that besides the substrate binding sites, some other residues distant from the binding pocket, including the ones in the hinge regions between the two domains, the front- and back- door channels and the exposed region, are important for the function of glutamine binding and transport. The predicted results are well consistent with the theoretical and experimental data, which indicates that our method is an effective approach to identify the key residues important for both ligand binding and long-range allosteric signal transmission. This work can provide some insights into the function performance of GlnBP and the physical mechanism of its allosteric regulation.